1992
DOI: 10.1021/bi00119a003
|View full text |Cite
|
Sign up to set email alerts
|

Transition-state characterization: a new approach combining inhibitor analogs and variation in enzyme structure

Abstract: A new strategy of potentially broad application for probing transition-state (TS) analogy in enzymatic systems is described in this paper. The degree to which a series of phosphonate inhibitors act as TS analogues of rat carboxypeptidase A1 has been determined for the wild-type enzyme, for the R127K, R127M, and R127A mutants, and for the R127A mutant in the presence of 0.5 M guanidine hydrochloride. The impact that the mutations have on the inverse second-order rate constants (Km/kcat) for substrate hydrolysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 30 publications
2
53
0
Order By: Relevance
“…Phosphorus-containing compounds have previously been characterized as noncovalent inhibitors and transition state analogs of other hydrolases, including aspartyl-and metalloproteases (24,25). A variety of crystallographic, kinetic, and structure/function data suggests that inhibitors containing tetrahedral phosphorus groups can share characteristics of tetrahedral transition state intermediates (24,27,28). Although the K i for HMPOBA is higher than expected for a true transition state analog, it is reasonable to conclude that our results approximate many of the geometric and electronic features expected for an intermediate of FAH-catalyzed reactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorus-containing compounds have previously been characterized as noncovalent inhibitors and transition state analogs of other hydrolases, including aspartyl-and metalloproteases (24,25). A variety of crystallographic, kinetic, and structure/function data suggests that inhibitors containing tetrahedral phosphorus groups can share characteristics of tetrahedral transition state intermediates (24,27,28). Although the K i for HMPOBA is higher than expected for a true transition state analog, it is reasonable to conclude that our results approximate many of the geometric and electronic features expected for an intermediate of FAH-catalyzed reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Substrate analogs containing phosphonate, phosphonoamidate, and phosphinate groups have been used as effective noncovalent inhibitors of aspartylproteases (24) and metalloproteases (25), whereas phosphonate and phosphinate bisubstrate inhibitors have been used to inhibit farnesyltransferase (26). Of particular interest to the enzymatic mechanism of FAH are studies indicating that the tetrahedral geometry associated with the phosphorus groups in these types of inhibitors closely approximates both geometric and electronic aspects of the transition state (24,27,28). Thus, the effectiveness of these compounds as inhibitors is presumably associated with similarities to the high energy reaction intermediates stabilized during catalysis.…”
mentioning
confidence: 99%
“…18 The authors noted that irregularities in their data suggested the existence of a minor 2:1 uridine:vanadate species as well. Recent work by Tracey and coworkers used 1 H, 13 C, and 51 V NMR spectroscopy to demonstrate that a 2:2 nucleoside:vanadate dimer predominates in solution under most conditions.40 A 2:2 species has also been observed by X-ray diffraction analysis.41 Tetrahedral and pentacoordinate 1:1 complexes do occur in solution, but only in minor proportions. 40 The formation constant for U>v has been estimated to be (1.8 ± 1.5) M −1 at pH 7.…”
Section: What Is the Value Of K I For Uridine 2′3′-cyclic Vanadate?mentioning
confidence: 99%
“…7,10,12,13 The failure of pentavalent organo-vanadates as transition state analogues for phosphoryl transfer reactions is explicable. The location and charge of the vanadyl oxygens differ significantly from those of the corresponding phosphoryl oxygens in the enzymic transition state.…”
Section: Organo-vanadates As Mimics Of Transition Statesmentioning
confidence: 99%
See 1 more Smart Citation